Knowledge is (Less) Power: Experimental Evidence from Residential Energy Use - Jessoe, Katrina; Rapson, David (American Economic Review, 2014)
Imperfect information about product attributes inhibits efficiency in many choice settings, but can be overcome by providing simple, low-cost information. We use a randomized control trial to test the effect of high-frequency information about residential electricity usage on the price elasticity of demand. Informed households are three standard deviations more responsive to temporary price increases, an effect that is not attributable to price salience. Conservation extends beyond pricing events in the short and medium run, providing evidence of habit formation and implying that the intervention leads to greenhouse gas abatement. Survey evidence suggests that information facilitates learning. (JEL D12, D83, L11, L94, Q41, Q54)